ECOLOGICAL ASPECTS OF CHEMICAL AND PHYSICO-CHEMICAL FORTIFICATION OF SOILS - Kiyomov Shavkat Fazliddinovich (Web of Journals Publishing, 2024)
This article covers the ecological aspects of chemical and physico-chemical reinforcement of grunts and the methods of chemical and physico-chemical reinforcement of grunts.
Keywords: grunt, gruntgrunt waters, environment, toxic (toxic) substances, alkali, resins, Sandy and lyose grunts, cement.